Library services for the disabled in the Malaysian selected public university libraries - Siti Mawarni binti Salim (Kulliyyah Information and Communication Technology, International Islamic University Malaysia, 2017)
According to Act 658, people with disabilities shall have the right to the access to information, communication and technology on equal basis with people without disabilities (Persons with Disabilities Act 2008, Act 685). The purpose of this study is to highlight all the services provided by the public university libraries in Malaysia for the disabled students as library members. At the same time, problems faced by the libraries and the disabled users were studied. Questionnaires were sent to five selected public university libraries and also distributed to the disabled students in each university to obtain feedback. From this study, it was found that the level of library services and facilities for the disabled users was rather low and the usage levels among the disabled users were also low. Some of the libraries provided services and facilities for the disabled users but they don't have registered members among the disabled students. The satisfaction level towards library services and facilities among the disabled users were also discussed. Some recommendations for improvement and for further research are provided in this report. The result findings from this study can be used to enhance and improve the current level of library services for the disabled users in the future. This initiative was taken to support the mission and vision of the university to produce quality research and knowledgeable students.